POTENSI KERETA API SEBAGAI MODA ANGKUTAN BARANG DITINJAU DARI SISI BIAYA (Studi Kasus: Tj. Enim dan Pelabuhan Panjang) - Suzi Heti Kurnia (SOSIALITA, 2018)
Development and the increasing of industry product, mining, agriculture, plantation in South of Sumatera, make Lampung Province have significant role for cargo delivery traffic. Geographical location of Lampung isin a tip of Sumatera which is the most crowded for cargo delivery, likewise Panjang Port as the biggest cargo port in Sumatera. The problem which is arise because of the delivery cargo to port still using truck which cause damaged road, air pollution, accident, traffic jam, and also the cost is very high. Therefor the delivery to port expected could use railway as one of transportation mode. Not only could load in a big volume but also the cost could be cheaper and good for environment. This study intends to count the feasibility of the railway as transportation mode to gate in the Panjang port, also to analyze the utilization of railway, and diversion transportation mode from truck to railway. Railways expected to be the most potential transportation mode for long term. The methods of this study develop from data and information and then will be reviewed by the relevant substance. This analyze done by counting delivery capacitycost, time, speed, and service roads. The purpose of analysis determines the feasibility to build a railway in Panjang Port based on component costs and benefits, the study period starting in February 2015.This feasibility study views in term of cost by counting Internal Rate of Return (IRR), Benefit Cost Ratio (BCR) and Net Present Value (NPV), and Payback Period. This calculation use data of export from Industrial and Commercial Department Lampung and data of domestic ship and foreign ship at Panjang Port with assumption average growth 7,6% based on operational cost and revitalization and double track investment. From the calculation, we get IRR, BCR and NPV which match with feasibility and will payback in 7th year. We could conclude that railway transportation mode is really potential as cargo transportation mode in Panjang Port and expected could improve the performance and develop Panjang port to support the smoothtransportation of goods.Keywords: Commodity Exports, Railway Potential, Feasibility Study.